2003
DOI: 10.1161/01.atv.0000080687.94313.67
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein Expression Prevents Diet-Induced Atherosclerotic Lesions in Male db/db Mice

Abstract: Objective-Accompanying more atherogenic lipoprotein profiles and an increased incidence of atherosclerosis, plasma cholesteryl ester transfer protein (CETP) is depressed in diabetic obese patients compared with nondiabetic obese counterparts. The depressed levels of CETP in the plasma of diabetic obese individuals may contribute to the development of an atherogenic lipoprotein profile and atherogenesis. We have examined the effect of CETP expression on vascular health in the db/db model of diabetic obesity. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…In other studies, expression of the CETP gene has been reported to have an antiatherogenic effect in db/db obese diabetic mice, 20 in lCAT transgenic mice, 21 in ovariectomized mice, 22 in testosterone-deficient mice, 23 and in apoC-III transgenic mice with hypertriglyceridemia. 24 In the last study, however, it was also reported that expression of the Cetp gene was proatherogenic in Figure 1.…”
Section: Studies In Rodentsmentioning
confidence: 92%
See 1 more Smart Citation
“…In other studies, expression of the CETP gene has been reported to have an antiatherogenic effect in db/db obese diabetic mice, 20 in lCAT transgenic mice, 21 in ovariectomized mice, 22 in testosterone-deficient mice, 23 and in apoC-III transgenic mice with hypertriglyceridemia. 24 In the last study, however, it was also reported that expression of the Cetp gene was proatherogenic in Figure 1.…”
Section: Studies In Rodentsmentioning
confidence: 92%
“…Mice fed an atherogenic diet 14 ApoE knockout mice 15 LDL receptor knockout mice 15 ApoC-III transgenic mice with normal plasma triglyceride levels 24 ApoE3-Leiden mice 16 Aypertensive rats 17 Expression of CETP in rodents had no effect on atherosclerosis SR-B1 knockout mice 18 Expression of CETP in rodents decreased atherosclerosis db/db obese, diabetic mice 20 LCAT transgenic mice 21 Ovariectomized mice 22 Testosterone-deficient mice 23 ApoC-III transgenic mice with hypertriglyceridemia 24 B. Rabbits (rabbits have a high natural level of CETP activity) Inhibition of CETP in rabbits decreased susceptibility to diet-induced atherosclerosis in:…”
Section: Expression Of Cetp In Rodents Increased Atherosclerosis Inmentioning
confidence: 99%
“…Rodents lack CETP (Ha and Barter, 1982) and are naturally resistant to the development of atherosclerosis. Transgenic expression of the Cetp gene in mice and rats has generated conflicting and modeldependent results, with some studies supporting the proposition that CETP is proatherogenic (Marotti et al, 1993;Herrera et al, 1999;Plump et al, 1999;Westerterp et al, 2006;Hildebrand et al, 2010;Kühnast et al, 2015), whereas others suggest that CETP has no effect or is antiatherogenic (Hayek et al, 1995;Föger et al, 1999;Cazita et al, 2003;MacLean et al, 2003;Casquero et al, 2006).…”
Section: B Therapies That Target High-density Lipoproteinmentioning
confidence: 99%
“…Transgenic mice have been engineered to express CETP, resulting in the development of atherosclerosis (86,87). Different murine models have provided discordant results, with some indicating that CETP is antiatherogenic (88)(89)(90), and others that it is proatherogenic (91)(92)(93). Rabbits are highly susceptible to the development of diet-induced atherosclerosis, and have a naturally high level of CETP.…”
Section: Targeting High-density Lipoprotein (Hdl) (Table 2)mentioning
confidence: 99%